Maternal Death Due to Amniotic Fluid Embolism: A National Study in France. Issue 2 (June 2018) - Bonnet, M.P.; Zlotnik, D.; Saucedo, M.; Chassard, D.; Bouvier-Colle, M.H.; Deneux-Tharaux, C.
Abstract : ( Anesth Analg . 2018;126(1):175–182) Signs and symptoms of amniotic fluid embolism (AFE) vary greatly and are not specific to AFE, making it a difficult condition to diagnose and treat. Recently, the Society for Maternal-Fetal Medicine (SMFM) and the AFE Foundation proposed 4 uniform diagnostic criteria to help identify cases of AFE for research purposes. These criteria have not been tested on a specific population. The authors of the present study applied these criteria to maternal deaths attributed to AFE between 2007 and 2011, as identified by a national experts committee from the French Confidential Enquiry into Maternal Deaths, to evaluate its potential as a diagnostic tool. Furthermore, they described the epidemiology, clinical characteristics, and management of AFE by the presence or absence of all 4 diagnostic criteria.